Cerebral Venous Infarction After AVM Resection: Pictorial - Beneš, Vladimír (Acta neurochirurgica. Supplement, 2025)
A case report of a 68-year-old otherwise-healthy female patient with Spetzler-Martin (SM) grade I arteriovenous malformation (AVM) in her left frontal region is presented. After an uneventful surgery, cerebral venous infarction developed, and the patient was rendered hemiparetic with motor aphasia. After bony decompression, slow improvement was seen, and 3 months after surgery, the patient was neurologically intact. Six months after AVM resection, cranioplasty was performed. Infarction was caused by the thrombosis of a long primary draining vein, which finished its course in the normal cortical venous system. The case supports the venous origin of postoperative bleeding after AVM resection instead of the normal perfusion pressure phenomenon.
Keywords: magnetická rezonanční tomografie; senioři; mozkové žíly; Cerebral Veins; Magnetic Resonance Imaging; Cerebral Infarction; ženské pohlaví; intrakraniální arteriovenózní malformace; venous occlusive disease; Humans; Intracranial Arteriovenous Malformations; Female; Aged; cerebrální infarkt; Cerebral arteriovenous malformation; Postoperative Complications; pooperační komplikace; lidé